Insulin-like growth factor 1 and a cytosolic tyrosine kinase activate chloride outward transport during maturation of hippocampal neurons - Kelsch, Wolfgang; Hormuzdi, Sheriar; Straube, Emine; Lewen, Andrea; Monyer, Hannah; Misgeld, Ulrich (The journal of neuroscience, 2001)
The development of hyperpolarizing inhibition is an important step in the maturation of neuronal networks. Hyperpolarizing inhibition requires Cl− outward transport that is accomplished by KCC2, a K+/Cl− cotransporter. We show that cultured hippocampal neurons initially contain an inactive form of the KCC2 protein, which becomes activated during subsequent maturation of the neurons. We also show that this process is accelerated by transient stimulation of IGF-1 receptors. Because the transporter can be rapidly activated by coapplication of IGF-1 and an Src kinase and can be deactivated by membrane-permeable protein tyrosine kinase inhibitors, we suggest that activation of K+/Cl− cotransporter function by endogenous protein tyrosine kinases mediates the developmental switch of GABAergic responses to hyperpolarizing inhibition.
Gesehen am 27.04.2021